2009
DOI: 10.1111/j.1399-0004.2008.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Skoura – a genetic island for congenital insensitivity to pain and anhidrosis among Moroccan Jews, as determined by a novel mutation in the NTRK1 gene

Abstract: Congenital insensitivity to pain with anhidrosis (CIPA) or hereditary sensory and autonomic neuropathy type IV is a rare, autosomal recessive neurologic disorder, characterized by absence of reaction to painful stimuli, mental retardation, self- mutilating behavior, anhidrosis, and recurrent episodes of hyperthermia. Mutations in the neurotrophic tyrosine kinase receptor 1, a receptor phosphorylated by nerve growth factor, have been documented in diverse ethnic groups. We identified the same novel nonsense mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The authors screened for mutations in the NTRK1 gene and revealed one novel frameshift mutation, two novel nonsense mutations, and three unrelated types with the same splice-site mutation; genotyping of the three families with the identical splice-site mutation showed that they share the same haplotype, suggesting that a specific mutation developed in Turkey. Similar mutations have been found in Morocco: in the March 2009 issue of Clinical Genetics, Suriu and colleagues, from the Institute of Human Genetics at the Western Galilee Hospital-Nahariya, Israel, identified an identical novel nonsense mutation in two unrelated families of Moroccan Jewish descent, each with two affected siblings [17]. The authors reason that the founder mutation may be traced to the rural Jewish village in southern Morocco from where both these families originated.…”
Section: Genetic Clustersmentioning
confidence: 83%
“…The authors screened for mutations in the NTRK1 gene and revealed one novel frameshift mutation, two novel nonsense mutations, and three unrelated types with the same splice-site mutation; genotyping of the three families with the identical splice-site mutation showed that they share the same haplotype, suggesting that a specific mutation developed in Turkey. Similar mutations have been found in Morocco: in the March 2009 issue of Clinical Genetics, Suriu and colleagues, from the Institute of Human Genetics at the Western Galilee Hospital-Nahariya, Israel, identified an identical novel nonsense mutation in two unrelated families of Moroccan Jewish descent, each with two affected siblings [17]. The authors reason that the founder mutation may be traced to the rural Jewish village in southern Morocco from where both these families originated.…”
Section: Genetic Clustersmentioning
confidence: 83%
“…Therefore, our case could represent a unique variant of HSAN type IV without mental retardation. [25] Due to lack of availability of genetic tests, mutational studies could not be done in our case. The present case history and clinical images illustrate that HSAN type IV, rarely seen in pediatric population, is one of the most debilitating neuropathies of childhood with a high morbidity and a shortened life span.…”
Section: Discussionmentioning
confidence: 99%
“…[23] We present clinical and nerve biopsy images of a 13-year-old boy with classical manifestations of CIPA.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a total of 62 different mutations of the NTRK1 gene have been reported in patients with CIPA (Greco et al, 2000;Miura et al, 2000b;Shatzky et al, 2000;Bodzioch et al, 2001;Indo, 2001;Indo et al, 2001;Mardy et al, 2001;Miranda et al, 2002;Bonkowsky et al, 2003;Guo et al, 2004;Huehne et al, 2008;Suriu et al, 2009;Lee et al, 2009;Lin et al, 2010). TKD of the NTRK1 protein is located in the codons from 501 to 796, which is approximately 37% of the full length of the TKD protein.…”
Section: Discussionmentioning
confidence: 99%